Small-bowel endoscopy - Eisen, G. M. (Endoscopy, 2012)
The 2012 Digestive Disease Week (DDW; 19 – 22 May, San Diego, California, USA) confirmed once again that the small bowel is no longer the frontier that it had been in years past. The clinician has multiple devices available, ranging from noninvasive imaging to device-assisted enteroscopy and video capsule endoscopy (VCE). The debate continues as to which device should be used and when. There were several well-conducted randomized trials assessing this, predominantly in the management of obscure gastrointestinal bleeding (OGIB). Many abstracts also focused on the diagnosis and follow-up assessment of Crohn’s disease. As usual there have been incremental improvements in VCE; however, there were no “game changers” introduced this year.